The Correlation Between Knowledge Level and Willingness to Receive COVID-19 Vaccine in School - Nurmalahayati Nurdin; Jihan Zia ‘Ufairah (Jurnal Pendidikan Humaniora, 2021)
Abstract: In Indonesia, vaccination against COVID-19 has become a requirement for all educational institutions. The vaccine can help instructors, education staff, and students prevent the spread of COVID-19 in schools. However, a person's awareness and willingness to receive the COVID-19 vaccine might be influenced by a number of other circumstances. The purpose of this study is to analyze the relationship between knowledge level and willingness to receive the COVID-19 vaccination among students at MAS Ulumul Quran in Banda Aceh. The research was conducted using a mixed method, involving all students of MAS Ulumul Quran, Banda Aceh, totaling 260 students. The study concluded that there is no significant correlation between knowledge and willingness to receive COVID-19 vaccination in students of MAS Ulumul Quran in Banda Aceh. This can also be interpreted that the level of knowledge of students has no correlation with their willingness to receive the COVID-19 vaccination.Key Words: Covid-19, knowledge, willingness, vaccination Abstrak: Di Indonesia, vaksinasi terhadap COVID-19 sudah menjadi keharusan bagi semua institusi pendidikan. Vaksin tersebut dapat membantu instruktur, tenaga kependidikan, dan siswa mencegah penyebaran COVID-19 di sekolah. Namun, kesadaran dan kesediaan seseorang untuk menerima vaksin COVID-19 mungkin dipengaruhi oleh sejumlah keadaan lain. Tujuan dari penelitian ini adalah untuk menganalisis hubungan tingkat pengetahuan dengan kesediaan menerima vaksinasi COVID-19 pada siswa MAS Ulumul Quran Banda Aceh. Penelitian dilakukan dengan metode campuran, melibatkan seluruh siswa MAS Ulumul Quran Banda Aceh yang berjumlah 260 siswa. Hasil penelitian menyimpulkan bahwa tidak ada hubungan yang signifikan antara pengetahuan dengan kemauan menerima vaksinasi COVID-19 pada siswa MAS Ulumul Quran di Banda Aceh. Hal ini juga dapat diartikan bahwa tingkat pengetahuan siswa tidak memiliki hubungan dengan kesediaannya untuk menerima vaksinasi COVID-19.Kata Kunci: Covid-19, pengetahuan, kemauan, vaksinasi